Evaluasi dalam Proses Pembelajaran Tematik di SDN Kampung Melayu 3 Tangerang - Ina Magdalena; Dita Lutfi Citra Anggraini; Noni Novitasari; Siti Nurlatifah (RC-INSTITUT, 2020)
This research aims to find out the effectiveness of the thematics learning approach in curriculum 2013 on its planning, implementation, and evaluation aspects. Actually the thematic learning approach gives a complete opportunity for participation and involvement of the student in their learning activity. Hence, several elementary schools (SD) have an effort to implement it, including SDN Kampung Melayu III, Kab. Tangerang, as a focus of this research project. But we don’t know-how about the implementation indeed. Therefore, the purpose of this research is to seek out the implementation of the thematic learning approach, its effectiveness on enhancing learning quality, and also its problems and learning results. Trough the quantitative research approach this research shown that the thematic learning process is effective based on the indicators coming from the CIPP procedure. But on the other side the problems coming from the limited learning facilities and infrastructures in school, including classroom arrangement and learning resources & media utilization by the teacher. The learning result from the final exams is good enough, moreover, it is also indicated that the learning process also rising up the student courage and self-confidence, they are so proactive in the learning process. The research conclusion are: the implementation of the thematic learning approach is effective, but the infrastructure is still needed for improvement to facilitate the learning process.